The strange case of Phragmipedium × talamancanum. An international story of conservation and taxonomy - Díaz Morales, Melissa (2019)
The importance of cultivated plants in the discovery and the description of orchid diversity cannot be overestimated. During the 19th century and the beginning of the last century, the fundamental task of exploring the richest regions in orchid flora around the world was essentially carried out by the great horticultural firms, which provided the botanists with an uninterrupted flow of novelties to be described and revealed to science. Although to a lesser extent, private collections, as well as the trained eyes of their owners, still continue to play an important role in the discovery of family diversity. In more recent years, with the spread of a generalized culture attentive to the problems of the sustainable use of natural resources, the orchid collectors discovered a new vocation aimed at conservation. In many cases private collections have been an important tool for the conservation ex situ of the rarest and most threatened orchid species; these species are important even when they are not the primary source of germplasm for the reproduction and reintroduction of species in their natural habitats. Particularly rare, however, is the case of cultivated plants that have served at the same time to preserve rare taxa and to clarify old problems of nomenclature. The story we present here represents one of these rare cases, and is made more significant by the fact that it involves a large number of different protagonists in two distant countries.